STRUCTURAL AND MAGNETIC PROPERTIES OF FE/SI MULTILAYER GROWN BY HELICON PLASMA SPUTTERING - Setyo Purwanto; Isao Sakamoto; M. Koike; H. Tanoue (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2003)
STRUCTURAL AND MAGNETIC PROPERTIES OF FE/SI MULTILAYER GROWN BY HELICON PLASMA SPUTTERING. Helicon plasma sputtering method has been used to grown the Fe/Si multilayer (MLs) with various thickness of Silicon spacer around 0.5 2nm for Fe thickness ﬁxed at 2nm in order to investigated the antiferromagnetic coupling behaviour. Also we grown the MLs with various Fe thickness around 2-5nm for Silicon spacer fixed at tSi =l nm and l.5nm. Present study found that in case of Silicon spacer thickness tSi= l nm multilayer ﬁlm exhibit antiferromagnetically ordering, beside this thickness the MLs are ferromagnetic. The maximum magnetoresistance ratio is 0.22%, it appears at the Fe thickness tFe=3nm and Si thickness tSi=l nm.